The voice of an “interrogator”. Public statements by Ramón Camps regarding the “Timerman case” during the dictatorship (1981-1982) (Quinto Sol, 2024)
This article examines statements made by the repressor Ramón Camps during a television appearance in 1981 and in his own book published in 1982. In these, the military officer attempted to refute allegations linking him to human rights abuses. Notably, these accusations stemmed from a book published in the United States by one of his victims, journalist Jacobo Timerman. In his assertions, Camps sought to justify and validate his actions during the years of the dictatorial regime, publicly sharing excerpts from the interrogations conducted on Jacobo Timerman during his unlawful detention. Our analysis, firstly, offers insight into the tensions and paradoxes inherent in Camps' statements, in which denials of torture coexist with the display of clandestine interrogations. Secondly, our study challenges the perception of "normalcy" attributed to certain repressive practices within the dictatorial context. Lastly, the materials examined reveal how the hidden face of clandestine centers was complemented by the overt face of dictatorial propaganda.
Keywords: dictatorship; torture; propaganda; antisemitism